FULFILLMENT OF CIVIL RIGHTS FOR BELIEFS IN BANGKA DISTRICT - Rafiqa Sari; Tiara Ramadhani; Darwance Darwance (Faculty of Law, Universitas Riau, 2023)
Adherents trust, at first no protected by law positive in Indonesia, with birth Decision Court Constitution No. 97/PU-XIV/2016 related Constitution Administration population. This thing give positive impact for adherents trust namely, protection and recognition by Indonesian law to adherents devotee trust, one related with recording marriage. Valid something marriage from adherents trust implications for rights civil law on child status as well as problem inheritance later. Destination from study this for knowing validity from marriage devotee trust in Bangka Regency based on law positive as well as fulfillment rights civil for adherents trust. Study this conducted with use method law juridical empirical through researching materials References as well as studies cases that develop in the community adherents trust. The results of the research produced in Bangka Regency are still there is marriage from devotee unreliable trust registered so that result in they no get rights civil law, such as right for get inheritance. Study this is very important conducted because still there is adherents trust whose marriage not yet legitimate nationally so that no protected rights civil from the parties, so that study this is very important done.